(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
The text summarizes the main lines of an unpublished and original research on the production of conceptual and architectural drawings by a group of Roman women architects born in the forties and working in Rome during the 1960s in a historical-cultural phase in which exchanges and cultural growth of the younger generations was nourished by the activity in “studies”. The research will enhance unpublished works and open unexplored glimpses of stories already written around well-known personalities and documented facts.